PHYTOCHEMICAL CONTENT AND ANTIOXIDANT ACTIVITY OF LOWLAND BLACK POTATO PEELS (PLECTRANTHUS ROTUNDIFOLIUS) WITH COW MANURE USING ULTRASONIC BATH EXTRACTION METHOD - Ngadiani, Ngadiani; Andriani, Vivin; Binawati, Diah Karunia (jfpublisher, 2023)
Introduction. Black potato (Plectranthus rotundifolius) is one of the tubers in Indonesia and not well known by the public. It causes inadequate use of black potato than any other tubers. The parts that are currently used are the potato flesh. Meanwhile, the black potato peels are not used. Although the black potato peels contain polyphenol saponins, flavonoids, and antioxidant compounds. Method. Phytochemicals can be separated using extraction methods, one of the modern extraction methods used is the ultrasonic bath method. The ultrasonic bath method is a method that uses ultrasonic waves with a frequency greater than 16-20 KHz. The objective of this research is to determine the phytochemical content and antioxidant activity of lowland black potato peels with cow manure using ultrasonic bath extraction method. The research was conducted experimentally using RAL (Completely Randomized Design) with 3 factors and 3 replications, which included the difference in extraction temperature (55°C); extraction time (15 and 20 minutes); and the ratio of materials and solvents (1:5 and 1:10). Results & Analysis.The data obtained were yield, total phenolics, total tannins, flavonoids and antioxidant activity of black potato peels extracted using ultrasonic bath method with different temperature, extraction time and solvent ratio. The data obtained were analyzed using the Anova test with a significance of α = 0.05. Discussion. The analysis indicated that the treatment of 5 kg/plot manure with an extraction time of 20 minutes, at a temperature of 55°C, and a ratio of ingredients and solvents is 1:10 provided the best quality at 4.13% moisture content, 17.90% yield, 0.177 g/g phenols total, 0.063 g/g tannins, 0.096 g/g flavonoids and 45.275 ppm antioxidant activity.